Why entrepreneurs need firms, and the theory of the firm needs entrepreneurship theory (Revista de Administração, 2016)
Firms are established by entrepreneurs, and entrepreneurship is typically embodied within a firm. And yet, the research literatures on entrepreneurship and the theory of the firm developed mostly independently. I suggest some reasons why these literatures have struggled to connect, and offer a potential path forward, one that describes the entrepreneurial act as the acquisition, combination, and recombination of heterogeneous resources under conditions of uncertainty.